Anomalous course of the intracranial internal carotid artery into the orbit: case report. (16th June 2011) - Blackburn, Spiros L; Dannenbaum, Mark; Schuette, Albert J; Dion, Jacques
Abstract : In this report, a case of anomalous internal carotid artery looping into the orbital apex is presented. The patient was a 41-year-old man with sudden onset headache, suggestive of aneurysmal subarachnoid hemorrhage (SAH). Imaging with CT demonstrated a perimesencephalic distribution of blood. Cerebral angiography confirmed non-aneurysmal, perimesencephalic SAH, but incidentally noted an anomalous left internal carotid artery with a course into the orbital cone. This is the only known example of this anatomic variation. Potential embryological explanations are discussed.